(untitled) (Estudios Gerenciales, 2017)
The purpose of this paper is to evaluate the degree of comprehension and enforcement of social responsibility (SR) practices in micro, small and medium companies in Barranquilla (Colombia), based on the Stakeholders theory. Using an exploratory factor analysis on 779 companies it was found that the variables with a stronger explanatory influence for socially responsible performance are employees, environment, and community. By contrast, corporate management, value chain, and government/public sector condition the development of SR actions. Particularly, there is a weak perception and lack of will among owners and company managers to undertake comprehensive programs of social responsibility, as well as the formalization of those actions with an impact on the SR.